2016
DOI: 10.3389/fcell.2016.00069
|View full text |Cite
|
Sign up to set email alerts
|

p38MAPK and Chemotherapy: We Always Need to Hear Both Sides of the Story

Abstract: The p38MAPK signaling pathway was initially described as a stress response mechanism. In fact, during previous decades, it was considered a pathway with little interest in oncology especially in comparison with other MAPKs such as ERK1/2, known to be target of oncogenes like Ras. However, its involvement in apoptotic cell death phenomena makes this signaling pathway more attractive for many cancer research laboratories. This apoptotic role allows to establish a link between p38MAPK and regular chemotherapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 97 publications
3
43
0
Order By: Relevance
“…Likewise, genotoxic agents (cisplatin and oxaliplatin) and topoisomerase II inhibitors (doxorubicin) were also able to activate p38 MAPK route (43,44). Nowadays, a dual-role of this route is known with the action as tumor suppressor or tumor promoter largely depending on the type of cancer and tumor stage (45). Interestingly, our results have shown a robust p38 MAPK activation and using the specific p38 MAPK inhibitor, SB202190, we were able to significantly restore cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, genotoxic agents (cisplatin and oxaliplatin) and topoisomerase II inhibitors (doxorubicin) were also able to activate p38 MAPK route (43,44). Nowadays, a dual-role of this route is known with the action as tumor suppressor or tumor promoter largely depending on the type of cancer and tumor stage (45). Interestingly, our results have shown a robust p38 MAPK activation and using the specific p38 MAPK inhibitor, SB202190, we were able to significantly restore cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…5-FU has been the clinical practice for the management of CRC (and other solid malignancies) for decades, and is currently used in combination with other chemotherapeutic agents [20,21]. 5-FU is a pyrimidine analogue that exerts its antitumoral function via both inhibiting thymidylate synthase, a crucial enzyme in DNA replication, and being misincorporated during polynucleotide biosynthesis, resulting into DNA damage and, ultimately, apoptosis [22]. The effects of 5-FU on molecular stress pathways have long been investigated: indeed, reports are quite unanimous about p38 MAPK being phosphorylated and activated upon 5-FU exposure in several different cell-types [23,24].…”
Section: -Fluorouracil Effects On the P38 Mapk Signaling Pathway In Crcmentioning
confidence: 99%
“…Apoptosis is a major mechanism of cell death in response to anticancer agents and several studies already reported the role of p38 in modulating the chemotherapeutic response of both conventional treatment and novel agents including tyrosine kinase inhibitors (TKI) as well as monoclonal antibodies [ 272 ]. p38 has been implied in cell apoptosis mediated by cis-platinium and 5-fluorouracil (5-FU) in breast and colon cancer cell lines [ 272 ]. Furthermore, inhibition of p38 has been associated with resistance to gemcitabine and cytarabine [ 272 , 273 ].…”
Section: The Endothelial P38 Pathway As a Major Regulator Of Tumor Prmentioning
confidence: 99%